Oracle 9i DBA Handbook - Theriault Marlene (MC Graw Hill, 2002)
This authorized guide from Oracle Press explains how implement all the new features of Oracle9i and manage a robust, high-performance Oracle database. You'll get new and revised material on installation, database creation, using STATSPACK, Recovery Manager, Oracle9i Application Server, external tables, flashback queries, and much more.